An Investigation into an Arabic-to-Persian Dictionary: Anis Almo’asherin - Ahmad Behnami; Hosseynali Rahimi (تاریخ ادبیات)
The fact that Arabic-to-Persian dictionaries contain ancient Persian words and, therefore, can pave the way for accessing the original meaning of these obsolete words makes it incumbent upon us to study them. One of the most valuable of all these dictionaries is Anis Almo’asherin, written by an anonymous author during the late Ilkhanate era, which has fallen into obscurity and remains unknown. Anis Almo’asherin is a thematic dictionary organized into 38 different subjects under four major parts. The oldest available version dates back to 704 AH, and it is assumed that the book was written shortly before this time. This manuscript, which has not been edited nor printed to this day, deserves further research and publishing owing to its relative archaism. This article, looking into the structure of the manuscript in question and analyzing its compilation in the first place, examines the methodology of lexicography used by the author, identifies some of the resources employed in his work, and eventually focuses on the book’s remarkable features, including a list of very uncommon words along with their definitions.